Effect of TRAIL in combination with DDP on the expression of MDR1 gene in gastric cancer cells - Cui, Yu-Fang; Yu, Long-Shan; Wang, Hui-Qun; Gou, Ya-Wen; Wang, Qiao-Ming; Zhang, Kai-Guang (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Introduction : Gastric cancer is one of the most common malignant tumor, and gastric cancer is the second most common cause of cancer mortality worldwide. Although chemotherapy is one of the most important treatment options for gastric cancer, and could improve the overall survival rate and quality of live, one significant reason for its failure is multidrug resistance (MDR). Aim: To study the effect of tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) combined with chemotherapeutic drug cisplatin (DDP) on the expression of multidrug resistance gene 1 (MDR1) in the gastric cancer cell line SGC-7901/VCR. Material and methods : SGC-7901/VCR cells were cultured with DDP and TRAIL in various concentrations. The apoptosis rate was separately measured by a flow cytometer in DDP (sub-toxic dose) alone, TRAIL (200 µg/l) alone and in a combination of the two. Expression levels of MDR1 mRNA and P-glycoprotein (P-gp) were detected by RT-PCR and ELISA analysis, respectively. Results: The apoptosis rate in the combination group was significantly higher than that in the other groups (p < 0.05). According to the results of RT-PCR and ELISA, the expressions of MDR1 mRNA and P-gp in the combination group were statistically significant different compared with other groups (p < 0.05). Conclusions : The combination of TRAIL with DDP could reverse MDR phenotype in gastric cancer cell line SGC7901/VCR. The mechanism may be involved in the down-regulation of MDR1 mRNA and P-gp, which may play an essential role in overcoming the chemotherapeutic resistance of gastric cancer cells. This study indicates that a combination of chemotherapy and TRAIL may be an effective strategy to treat MDR gastric cancer.